Advances in development of long-term embryonic stem cell-like cultures from a marine fish, Sciaenops ocellatus - Catherine J. Walsh; Nicole Rhody; Kevan L. Main; Jessica Restivo; Andrea M. Tarnecki (Current Research in Food Science)
The overall goal of our research was to develop an embryonic stem cell line from red drum, Sciaenops ocellatus. These experiments were conducted to support future production of cell-based cultivated seafood products as a means towards meeting the growing global demand for sustainable seafood. Our hypothesis was that characteristics of embryonic stem cells, such as high proliferation and pluripotency, would facilitate development of a continuous cell line that could eventually be directed toward a muscle cell phenotype. We isolated embryonic stem cells from fertilized red drum eggs at the blastomere stage. These cells were seeded into culture wells at 50,000 cells/well. We tested various media, supplements, growth factors, and plate coatings to achieve growth of red drum embryonic cells. Cells at isolation reacted positively with the stem cell markers, OCT4, Nanog, and Sox2. Our cells had a fibroblast-like appearance and were maintained in culture for more than 43 days before senescence. Over time, most of the cultures showed extensive differentiation or died. The establishment of in vitro cultures of embryonic stem cell-like cells derived from red drum embryos represents progress towards developing cultured seafood products from marine fish.